Screening for CCNF Mutations in a Chinese Amyotrophic Lateral Sclerosis Cohort - Tian, Danyang; Li, Jiao; Tang, Lu; Zhang, Nan; Fan, Dongsheng (Frontiers in Aging Neuroscience, 2018)
Previous research has identified CCNF mutations in familial (FALS) and sporadic amyotrophic lateral sclerosis (SALS), as well as in frontotemporal dementia (FTD). The aim of our study was to measure the frequency of CCNF mutations in a Chinese population. In total, 78 FALS patients, 581 SALS patients and 584 controls were included. We found 19 missense mutations, 9 synonymous mutations and 2 intron variants. According to the American College of Medical Genetics and Genomics standards and guidelines for the interpretation of sequence variants, 8 variants were judged to be pathogenic or likely pathogenic variants. The frequency of such variants was 2.56% in FALS and 1.03% in SALS. In conclusion, CCNF mutations are common in FALS and SALS patients of Chinese origin, and further study is still needed.